A novel two-dimensional approach to modelling functionally graded beams resting on a soil medium - Chegenizadeh, Amin; Ghadimi, Behzad; Nikraz, Hamid; Simsek, M. (Techno Press, 2014)
The functionally graded beam (FGB) is investigated in this study on both dynamic and static loading in case of resting on a soil medium rather than on the usual Winkler-Pasternak elastic foundation. The powerful ABAQUS software was used to model the problem applying finite element method. In the present study, two different soil models are taken into account. In the first model, the soil is assumed to be an elastic plane stress medium. In the second soil model, the Drucker-Prager yield criterion, which is one of the most well-known elastic-perfectly plastic constitutive models, is used for modelling the soil medium. The results are shown to evaluate the effects of the different soil models, stiffness values of the elastic soil medium on the normal and shear stress and free vibration properties. A comparison was made to those from the existing literature. Numerical results show that considering real soil as a continuum space affects the results of the bending and the modal properties significantly.